Assessment of outdoor patient's satisfaction regarding clinical investigation of physicians in government hospitals of Quetta, Pakistan - Ali Nawaz; Anila Alam; Shah Dawood; Musa Bin Bashir; Mirwais Khan; Maivand Khan (Archives of Nursing Practice and Care - Peertechz Publications, 2021)
Objective: The main objective of the study is to measurement of the satisfaction of Outpatient Department patients regarding clinical investigation of physicians in government hospitals of Quetta, Pakistan. Methods: It was a cross sectional questionnaire based study. Data was collected from OPD (Outpatient Departments) of government hospitals (Sandeman provisional hospital, Bolan medical complex hospital) of Quetta, through a pre-structured questionnaire. Total sample size of the study was 447. The data collected, was analysed by using IBM SPSS 22. The descriptive analysis was carried out for the demographic details as well as for other categories. All the data was categorical so was expressed as frequency and percentage. Results: A total of 447 OPD patients were included in the study to know their perceptions towards the doctors and their attitude while consultation. Total of 550 questionnaires were distributed with the response rate of 89.4%. It was found that most of respondents 270 (60.3%) were male and having majority 338 (75.4%) among the age group of 15 to 35 years. Majority 120 (26.8%) respondents were satisfied that physician making them feel ease during physical examination. Among all 175 (39.1%) answered positively (Good) to physician guided you regarding any of dietary change. Conclusion: This study reveals that there is a good satisfaction of patients regarding physician's attitude, diagnosis, treatment and advice in government hospitals of Quetta city.